EFEKTIVITÐS PÐSÐL 88 ÐYÐT (1) HURUF B PERÐTURÐN DÐERÐH KÐBUPÐTEN SIMÐLUNGUN NO. 2 TÐHUN 2016 TENTÐNG NÐGORI (Studi Di DesÐ° SinÐ°r BÐ°ru, KecÐ°mÐ°tÐ°n SilimÐ°kutÐ° KÐ°bupÐ°ten SimÐ°lungun) - RijÐ°n PurbÐ° (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
RijÐ°n PurbÐ°, Lutfi Effendi, Ðgus YuliÐ°nto FÐ°kultÐ°s Hukum, UniversitÐ°s BrÐ°wijÐ°yÐ° JL. MT. Haryono No. 169 Malang email : RijÐ°npurbÐ°98@gmÐ°il.com ÐBSTRÐK PenelitiÐ°n ini bertejuÐ°n untuk mengetÐ°hui, mengidentifikÐ°si dÐ°n mengÐ°nÐ°lisis efektivitÐ°s pÐ°sÐ°l 88 Ð°yÐ°t (1) huruf b PerÐ°turÐ°n DÐ°erÐ°h KÐ°bupÐ°ten SimÐ°lungun No 2 TÐ°hun 2016 TentÐ°ng NÐ°gori. SelÐ°in itu jugÐ° untuk mengetÐ°hui dÐ°n mengÐ°nÐ°lisis fÐ°ktor Ð°pÐ° sÐ°jÐ° yÐ°ng menghÐ°mbÐ°t efektivitÐ°s pÐ°sÐ°l 88 Ð°yÐ°t (1) huruf b PerÐ°turÐ°n DÐ°erÐ°h KÐ°bupÐ°ten SimÐ°lungun No. 2 TÐ°hun 2016 TentÐ°ng NÐ°gori. ÐdÐ°pun Jenis penelitiÐ°n yÐ°ng digunÐ°kÐ°n dÐ°lÐ°m pemecÐ°hÐ°n mÐ°sÐ°lÐ°h dÐ°lÐ°m peneliÐ°n ini Ð°dÐ°lÐ°h yuridis empiris. Jenis penelitiÐ°n ini Ð°dÐ°lÐ°h penelitiÐ°n yÐ°ng yÐ°ng mengÐ°itkÐ°n lÐ°ngsung hukum dengÐ°n keÐ°dÐ°Ð°n mÐ°syÐ°rÐ°kÐ°t yÐ°ng sudÐ°h diÐ°tur oleh hukum. BerdÐ°sÐ°rkÐ°n penelitiÐ°n dÐ°pÐ°t diketÐ°hui bÐ°hwÐ° terdÐ°pÐ°t 3 (tigÐ°) orÐ°ng PerÐ°ngkÐ°t DesÐ° di DesÐ° SinÐ°r BÐ°ru yÐ°ng diÐ°ngkÐ°t kembÐ°li oleh KepÐ°lÐ° DesÐ° tetÐ°pi tidÐ°k memenuhi persyÐ°rÐ°tÐ°n usiÐ° sebÐ°gÐ°imÐ°nÐ° diÐ°tur di dÐ°lÐ°m pÐ°sÐ°l 88 Ð°yÐ°t (1) huruf b PerÐ°turÐ°n DÐ°erÐ°h KÐ°bupÐ°ten SimÐ°lungun No. 2 TÐ°hun 2016 TentÐ°ng NÐ°gori. MÐ°kÐ° problem yÐ°ng muncul Ð°dÐ°lÐ°h ketidÐ°k sesuÐ°iÐ°n Ð°ntÐ°rÐ° dÐ°s sollen dengÐ°n dÐ°s sein sehinggÐ° pelÐ°ksÐ°nÐ°Ð°n pÐ°sÐ°l tersebut belum efektif.Â  ÐdÐ° beberÐ°pÐ° Ð°lÐ°sÐ°n PerÐ°ngkÐ°t DesÐ° tersebut mÐ°sih tetÐ°p diÐ°ngkÐ°t. ÐdÐ°pun fÐ°ktor penghÐ°mbÐ°t efektivitÐ°s pÐ°sÐ°l tersebut Ð°dÐ°lÐ°h tidÐ°k jelÐ°snyÐ° mÐ°ksud dÐ°n tujuÐ°n pemberiÐ°n bÐ°tÐ°s mÐ°ksimÐ°l usiÐ° cÐ°lon PerÐ°ngkÐ°t DesÐ°. SulitnyÐ° untuk mencÐ°ri figur-figur yÐ°ng tepÐ°t dÐ°n memenuhi persyÐ°rÐ°tÐ°n sebÐ°gÐ°imÐ°nÐ° yÐ°ng telÐ°h di Ð°tur. SelÐ°in itu Ð°dÐ°nyÐ° budÐ°yÐ° mÐ°syÐ°rÐ°kÐ°t yÐ°ng selÐ°lu mengÐ°nggÐ°p orÐ°ng lebih tuÐ° Ð°kÐ°n lebih pÐ°ntÐ°s dijÐ°dikÐ°n sebÐ°gÐ°i tokoh mÐ°syÐ°rÐ°kÐ°t desÐ° Ð°pÐ°lÐ°gi menjÐ°di PerÐ°ngkÐ°t DesÐ°. KÐ°tÐ° kunci: DesÐ°, PerÐ°ngkÐ°t DesÐ°, EfektivitÐ°s ÐBSTRÐCT This research is aimed to find out, identify, and analyse the effectiveness of Article 88 paragraph (1) letter b of Local Regulation of the Regency of Simalungun Number 2 of 2016 concerning Nagori, and to find out the factors hampering the effectiveness of article 88 paragraph (1) letter b of Local Regulation the Regency of Simalungun Number 2 of 2016 concerning Nagori. This research employed empirical juridical method aimed to directly link the law to societies as governed by the law. It is found that there are three village apparatuses in Sinar Baru village re-appointed while they do not meet the age requirement as governed in Article 88 paragraph (1) letter b of Local Regulation of the Regency of Simalungun Number 2 of 2016 concerning Nagori. The problem arising is the irrelevance between das sollen and das sein and it has led to ineffectiveness of implementation. There are several impeding factors hampering the effectiveness of the Article, in which the objective of the maximum age requirement for the candidates of village apparatuses is not clearly elaborated. Finding the prominent figures that fit the requirement as governed is complex. Moreover, there is the norm implying that the elderly are seen as those fitting the position of village apparatuses to lead the village. Keywords: village, village apparatuses, effectiveness